(untitled) (Acta Scientiarum. Biological Sciences, 2015)
Current study assesses the biodiversity and selects lipase-producer microorganisms with industrial interest, from the savannah of the state of Tocantins, Brazil. Seventeen pequi microorganisms (Caryocar brasiliense) were isolated in the decomposition stage and 35 microorganisms were retrieved from the soil fraction under the collected pequi. Yarrowia lypolitica strain was used as positive control in all assays. The 52 strains were subjected to tests in a solid medium with Tween 20 for checking halos formed by crystals, indicating lipase production by inoculated strains. Another test to confirm lipase producers was conducted in microplates with liquid medium and enriched with p-nitrophenyl palmitate (pNPP) monitored at 410 Î·m. The AS16 and AP5 strains showed the highest activity for test conditions, namely, 0.072 and 0.067 U mL-1 respectively. Rates were higher than the lipase activity of Yarrowia lypolitica(0.052 U mL-1), a reference strain in current assay.